USE OF THE SYSTEM RESERVATIONS IN THE FRONT OFFICE DEPARTMENT OF THE GRAND SUKA HOTEL PEKANBARU - Farhan, Ibnu; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research aims to find out about the procedures for ordering forms for the Front Office Department at the Grand Suka Hotel Pekanbaru. The reservation form is the process of creating a list of incoming guest orders in accordance with existing procedures. Suka is an abbreviation for